Rumusan Iman yang Benar Menurut Yakobus 1:19-27 - Iksantoro, Iksantoro; Kamo, Yunus (Sekolah Tinggi Teologi Berita Hidup, 2024)
The debate about faith and actions which gives the impression of differences in theological views between Paul and James, can be resolved by understanding the correct formulation of faith in the book of James 1:19-27. To find the formula of true faith, the researcher used a text exegesis method using the principles of Hermeneutics. Based on the results of the analysis of the text of James 1:19-27, it was found that the correct formula for faith is: listening, speaking and doing.Â Perdebatan tentang iman dan perbuatan yang menimbulkan kesan adanya perbedaan pandangan teologi antara Paulus dan Yakobus, dapat diselesaikan dengan memahami rumusan iman yang benar dalam kitab Yakobus 1:19-27.Â Metode yang digunakan dalam penelitian ini adalah eksegesa teks dengan menggunakan prinsip-prinsip Hermeneutika. Berdasarkan hasil analisis teks Yakobus 1:19-27 ditemukan urutan rumusan iman yang benar yaitu: mendengar, berkata-kata dan berbuat.